In situ measurement and sampling of acidic alteration products at Río Tinto in support of the scientific activity of the Ma_MISS instrument - Ferrari, Marco; De Angelis, Simone; Frigeri, Alessandro; Bruschini, Enrico; Gómez, Felipe; De Sanctis, Maria Cristina (Frontiers in Astronomy and Space Sciences, 2023)
We describe the procedures and results of a geological field analysis campaign in the Río Tinto area. This geologically/biologically well-documented site with its rock/water/biology interaction represents an ideal open-air laboratory where to collect spectral data and samples useful for testing space instruments. During the field campaign, we collected a large set of VIS-NIR (0.35 – 2.5 μm) measurements using the ASD FieldSpec4 portable spectrometer both on biosignature-bearing rocks and on alteration hydrated products (sulfates, clays, oxides, etc.). Furthermore, as a comparison to the data collected in the field, we report the results of the micro-Raman analyses carried out in the laboratory on the collected mineral/rock samples. This work was conducted in the framework of the Mars Multispectral Imager for Subsurface Studies (Ma_MISS) instrument that is a miniaturized visible and near-infrared (VIS-NIR) spectrometer (0.5 – 2.3 μm) devoted to the Martian subsurface exploration and integrated into the drilling system of the ESA Rosalind Franklin rover mission. Ma_MISS will acquire spectral data on the Martian subsurface from the excavated borehole wall. The scientific results obtained by this campaign confirm that the Río Tinto site is important for enriching the scientific community's grasp on the Martian environment and for obtaining key information on the mineralogical and geochemical evolution of the Martian surface/subsurface. In addition, this work provides crucial preparation for the exploitation and interpretation of the scientific data that the Ma_MISS instrument will supply during the active phase of the mission. This activity is also useful for defining the priorities of the astrobiological objectives on the ground.